Family game night and other catastrophes - Lambert, Mary E., 1984- (Scholastic Press, 2017)
Seventh-grader Annabelle's mother is a hoarder, and their whole house is full of canned goods, broken toys, fabric, and old newspapers--but when a pile of newspapers (organized by weather reports) falls on Annabelle's younger sister Leslie and their mother is more concerned about the newspapers, it sets off a chain of events that brings their fix-it-all grandmother in and Annabelle realizes that if there is any hope for change she can not isolate herself and keep her family's problems secret.